Application of the GUT technique in pathological manifestations in reinforced concrete structures and their corrections (Research, Society and Development, 2021)
Reinforced concrete is a constructive system widely used around the world. However, this constructive technique has constant failures and pathological manifestations. These problems may occur due to possible design flaws, mistakes in structural design, failures in execution process, as well as the lack of maintenance. Many researchers reported the high incidence of steel corrosion in reinforced concrete structures as one of the main pathological manifestations in all over the world. There is a lack of decision-making as to which manifestations need to be repaired urgently and which ones can wait for future repairs without aggravating the damage to the structure. Given this scenario, this work aimed to carry out a visual inspection in a reinforced concrete building, identifying its pathological manifestations and classifying these with the decision-making tool GUT (Gravity, Urgency, and Tendency). During the inspection generalized corrosion was identified in the reinforced concrete structural parts: slab, beams, and columns. By applying the GUT tool, it was possible to identify the priority of repairs on slabs, beams, and columns. The pathological manifestations observed were possibly caused by the incorporation of aggressive agents at the time of building the residence.